2019
DOI: 10.2217/fmb-2018-0261
|View full text |Cite
|
Sign up to set email alerts
|

Virological Surveillance of Human Respiratory Syncytial Virus A and B at a Tertiary Hospital in Catalonia (Spain) During Five Consecutive Seasons (2013–2018)

Abstract: Aim: Human respiratory syncytial virus (HRSV) is the main cause of respiratory tract infections among infants. Materials & methods: In the present study, the molecular epidemiology of HRSV detected from 2013 to 2017 has been described. Results: A 10% of collected samples were laboratory confirmed for HRSV. Patients under 2 years of age were the main susceptible population to respiratory syncytial virus disease, but an increasingly number of confirmed patients over 65 years of age was reported. Epidemics us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
26
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
4
26
1
1
Order By: Relevance
“…The remarkable number of tested samples (8212) during the 2017/18 season could be explained with the consciousness-raising of relevance of RSV disease among physicians. Therefore, from our point of view, the prevalence of this season (14.4%) might be the best representative in the country, being similar to findings from Senegal [33], Thailand [34], Spain [35] and different regions in India [36,37]. Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season.…”
Section: Discussionsupporting
confidence: 67%
“…The remarkable number of tested samples (8212) during the 2017/18 season could be explained with the consciousness-raising of relevance of RSV disease among physicians. Therefore, from our point of view, the prevalence of this season (14.4%) might be the best representative in the country, being similar to findings from Senegal [33], Thailand [34], Spain [35] and different regions in India [36,37]. Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season.…”
Section: Discussionsupporting
confidence: 67%
“…14 These samples should be analyzed with PCR or immunofluorescent antigen detection of orthopneumovirus. 7 The IHC results in combination with the clinical signs, microscopic lesions, and the PCR data strongly support the conclusion that the gibbon group in our case became acutely ill as a result of human orthopneumovirus infection.…”
supporting
confidence: 86%
“…A large study from South Africa (with 13,664 patients) between February 2009 to May 2012 showed that RSV was detected in 16% of the recruited subjects with more than 50% of them below 4 years of age [27]. G protein in the RSV is responsible for the virus attachment to the ciliated cells of the host airways and mediates virus adherence [28]. Therefore, G protein is the target for neutralizing antibodies but because of its high genetic variability and higher numbers of glycosylation sites it gives the virus the ability to evade the immune system and delay antigen recognition [29].…”
Section: Discussionmentioning
confidence: 99%